Respuesta :
Answer:
y = - 6, y = 4
Step-by-step explanation:
Given
2y² + 4y - 48 = 0 ( divide through by 2 )
y² + 2y - 24 = 0
Consider the factors of the constant term (- 24) which sum to give the coefficient of the y- term (+ 2)
The factors are + 6 and - 4 , since
6 × - 4 = - 24 and 6 - 4 = + 2 , thus
(y + 6)(y - 4) = 0
Equate each factor to zero and solve for y
y + 6 = 0 ⇒ y = - 6
y - 4 = 0 ⇒ y = 4
Answer:
Step-by-step explanation:
2y² + 4y - 48 = 0
2y² + 12y - 8y + (-8)* 6 = 0
2y(y + 6) - 8(y + 6) =0
(y + 6) (2y - 8)= 0
y + 6 = 0 ; 2y- 8 = 0
y = -6 2y = 8
y = 8/2
y = 4
Solution: y = -6 , 4